Haplotype-resolved diverse human genomes and integrated analysis of structural variation. - Ebert, Peter; Audano, Peter A; Zhu, Qihui; Rodriguez-Martin, Bernardo; Porubsky, David; Bonder, Marc Jan; Sulovari, Arvis; Ebler, Jana; Zhou, Weichen; Serra Mari, Rebecca; Yilmaz, Feyza; Zhao, Xuefang; et al. (Science, 2021)
Long-read and strand-specific sequencing technologies together facilitate the de novo assembly of high-quality haplotype-resolved human genomes without parent-child trio data. We present 64 assembled haplotypes from 32 diverse human genomes. These highly contiguous haplotype assemblies (average minimum contig length needed to cover 50% of the genome: 26 million base pairs) integrate all forms of genetic variation, even across complex loci. We identified 107,590 structural variants (SVs), of which 68% were not discovered with short-read sequencing, and 278 SV hotspots (spanning megabases of gene-rich sequence). We characterized 130 of the most active mobile element source elements and found that 63% of all SVs arise through homology-mediated mechanisms. This resource enables reliable graph-based genotyping from short reads of up to 50,340 SVs, resulting in the identification of 1526 expression quantitative trait loci as well as SV candidates for adaptive selection within the human population.
Keywords: Female; Genetic Variation; Genome, Human; Genotype; Haplotypes; High-Throughput Nucleotide Sequencing; Humans; INDEL Mutation; Interspersed Repetitive Sequences; Male; Population Groups; Quantitative Trait Loci; Retroelements; Sequence Analysis, DNA; Sequence Inversion; Whole Genome Sequencing

CNVs cause autosomal recessive genetic diseases with or without involvement of SNV/indels. - Yuan, Bo; Wang, Lei; Liu, Pengfei; Shaw, Chad; Dai, Hongzheng; Cooper, Lance; Zhu, Wenmiao; Anderson, Stephanie A; Meng, Linyan; Wang, Xia; Wang, Yue; Xia, Fan; et al. (Genet Med, 2020)
PURPOSE: Improved resolution of molecular diagnostic technologies enabled detection of smaller sized exonic level copy-number variants (CNVs). The contribution of CNVs to autosomal recessive (AR) conditions may be better recognized using a large clinical cohort. METHODS: We retrospectively investigated the CNVs' contribution to AR conditions in cases subjected to chromosomal microarray analysis (CMA, N = ~70,000) and/or clinical exome sequencing (ES, N = ~12,000) at Baylor Genetics; most had pediatric onset neurodevelopmental disorders. RESULTS: CNVs contributed to biallelic variations in 87 cases, including 81 singletons and three affected sibling pairs. Seventy cases had CNVs affecting both alleles, and 17 had a CNV and a single-nucleotide variant (SNV)/indel in trans. In total, 94.3% of AR-CNVs affected one gene; among these 41.4% were single-exon and 35.0% were multiexon partial-gene events. Sixty-nine percent of homozygous AR-CNVs were embedded in homozygous genomic intervals. Five cases had large deletions unmasking an SNV/indel on the intact allele for a recessive condition, resulting in multiple molecular diagnoses. CONCLUSIONS: AR-CNVs are often smaller in size, transmitted through generations, and underrecognized due to limitations in clinical CNV detection methods. Our findings from a large clinical cohort emphasized integrated CNV and SNV/indel analyses for precise clinical and molecular diagnosis especially in the context of genomic disorders.
Keywords: Child; DNA Copy Number Variations; Exons; Humans; INDEL Mutation; Retrospective Studies; Whole Exome Sequencing

Clinical exome sequencing reveals locus heterogeneity and phenotypic variability of cohesinopathies. - Yuan, Bo; Neira, Juanita; Pehlivan, Davut; Santiago-Sim, Teresa; Song, Xiaofei; Rosenfeld, Jill; Posey, Jennifer E; Patel, Vipulkumar; Jin, Weihong; Adam, Margaret P; Baple, Emma L; Dean, John; et al. (Genet Med, 2019)
PURPOSE: Defects in the cohesin pathway are associated with cohesinopathies, notably Cornelia de Lange syndrome (CdLS). We aimed to delineate pathogenic variants in known and candidate cohesinopathy genes from a clinical exome perspective. METHODS: We retrospectively studied patients referred for clinical exome sequencing (CES, N = 10,698). Patients with causative variants in novel or recently described cohesinopathy genes were enrolled for phenotypic characterization. RESULTS: Pathogenic or likely pathogenic single-nucleotide and insertion/deletion variants (SNVs/indels) were identified in established disease genes including NIPBL (N = 5), SMC1A (N = 14), SMC3 (N = 4), RAD21 (N = 2), and HDAC8 (N = 8). The phenotypes in this genetically defined cohort skew towards the mild end of CdLS spectrum as compared with phenotype-driven cohorts. Candidate or recently reported cohesinopathy genes were supported by de novo SNVs/indels in STAG1 (N = 3), STAG2 (N = 5), PDS5A (N = 1), and WAPL (N = 1), and one inherited SNV in PDS5A. We also identified copy-number deletions affecting STAG1 (two de novo, one of unknown inheritance) and STAG2 (one of unknown inheritance). Patients with STAG1 and STAG2 variants presented with overlapping features yet without characteristic facial features of CdLS. CONCLUSION: CES effectively identified disease-causing alleles at the mild end of the cohensinopathy spectrum and enabled characterization of candidate disease genes.
Keywords: Adolescent; Alleles; Antigens, Nuclear; Biological Variation, Population; Carrier Proteins; Cell Cycle Proteins; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Cohort Studies; De Lange Syndrome; Exome; Female; Gene Frequency; Genetic Heterogeneity; Humans; INDEL Mutation; Male; Mutation; Nuclear Proteins; Phenotype; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins; Retrospective Studies; Whole Exome Sequencing

De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith-Magenis syndrome. - Vetrini, Francesco; McKee, Shane; Rosenfeld, Jill A; Suri, Mohnish; Lewis, Andrea M; Nugent, Kimberly Margaret; Roeder, Elizabeth; Littlejohn, Rebecca O; Holder, Sue; Zhu, Wenmiao; Alaimo, Joseph T; Graham, Brett; et al. (Genome Med, 2019)
BACKGROUND: Neurodevelopmental disorders are genetically and phenotypically heterogeneous encompassing developmental delay (DD), intellectual disability (ID), autism spectrum disorders (ASDs), structural brain abnormalities, and neurological manifestations with variants in a large number of genes (hundreds) associated. To date, a few de novo mutations potentially disrupting TCF20 function in patients with ID, ASD, and hypotonia have been reported. TCF20 encodes a transcriptional co-regulator structurally related to RAI1, the dosage-sensitive gene responsible for Smith-Magenis syndrome (deletion/haploinsufficiency) and Potocki-Lupski syndrome (duplication/triplosensitivity). METHODS: Genome-wide analyses by exome sequencing (ES) and chromosomal microarray analysis (CMA) identified individuals with heterozygous, likely damaging, loss-of-function alleles in TCF20. We implemented further molecular and clinical analyses to determine the inheritance of the pathogenic variant alleles and studied the spectrum of phenotypes. RESULTS: We report 25 unique inactivating single nucleotide variants/indels (1 missense, 1 canonical splice-site variant, 18 frameshift, and 5 nonsense) and 4 deletions of TCF20. The pathogenic variants were detected in 32 patients and 4 affected parents from 31 unrelated families. Among cases with available parental samples, the variants were de novo in 20 instances and inherited from 4 symptomatic parents in 5, including in one set of monozygotic twins. Two pathogenic loss-of-function variants were recurrent in unrelated families. Patients presented with a phenotype characterized by developmental delay, intellectual disability, hypotonia, variable dysmorphic features, movement disorders, and sleep disturbances. CONCLUSIONS: TCF20 pathogenic variants are associated with a novel syndrome manifesting clinical characteristics similar to those observed in Smith-Magenis syndrome. Together with previously described cases, the clinical entity of TCF20-associated neurodevelopmental disorders (TAND) emerges from a genotype-driven perspective.
Keywords: Adolescent; Child; Child, Preschool; Craniofacial Abnormalities; Developmental Disabilities; Female; Humans; INDEL Mutation; Infant; Intellectual Disability; Male; Muscle Hypotonia; Smith-Magenis Syndrome; Transcription Factors; Young Adult

Sequence variants in nine different genes underlying rare skin disorders in 10 consanguineous families. - Shah, Khadim; Mehmood, Sabba; Jan, Abid; Abbe, Izoduwa; Hussain Ali, Raja; Khan, Anwar; Chishti, Muhammad S; Lee, Kwanghyuk; Ahmad, Farooq; Ansar, Muhammad; Shahzad, Shaheen; Nickerson, Deborah A; et al. (Int J Dermatol, 2017)
BACKGROUND: Genodermatoses represent genetic anomalies of skin tissues including hair follicles, sebaceous glands, eccrine glands, nails, and teeth. Ten consanguineous families segregating various genodermatosis phenotypes were investigated in the present study. METHODS: Homozygosity mapping, exome, and Sanger sequencing were employed to search for the disease-causing variants in the 10 families. RESULTS: Exome sequencing identified seven homozygous sequence variants in different families, including: c.27delT in FERMT1; c.836delA in ABHD5; c.2453C>T in ERCC5; c.5314C>T in COL7A1; c.1630C>T in ALOXE3; c.502C>T in PPOX; and c.10G>T in ALDH3A2. Sanger sequencing revealed three homozygous variants: c.1718 + 2A>G in FERMT1; c.10459A>T in FLG; and c.92delT in the KRT14 genes as the underlying genetic cause of skin phenotypes. CONCLUSION: This study supports the use of exome sequencing as a powerful, efficient tool for identifying genes that underlie rare monogenic skin disorders.
Keywords: 1-Acylglycerol-3-Phosphate O-Acyltransferase; Aldehyde Oxidoreductases; Blister; Collagen Type VII; Consanguinity; DNA Mutational Analysis; DNA-Binding Proteins; Endonucleases; Epidermolysis Bullosa; Epidermolysis Bullosa Dystrophica; Epidermolysis Bullosa Simplex; Exome; Female; Flavoproteins; Homozygote; Humans; Ichthyosiform Erythroderma, Congenital; Ichthyosis Vulgaris; Ichthyosis, Lamellar; INDEL Mutation; Intermediate Filament Proteins; Keratin-14; Lipid Metabolism, Inborn Errors; Lipoxygenase; Male; Membrane Proteins; Mitochondrial Proteins; Muscular Diseases; Neoplasm Proteins; Nuclear Proteins; Pedigree; Periodontal Diseases; Phenotype; Photosensitivity Disorders; Porphyria, Variegate; Protoporphyrinogen Oxidase; Rare Diseases; Sjogren-Larsson Syndrome; Skin Diseases, Genetic; Transcription Factors; Xeroderma Pigmentosum

A general framework for estimating the relative pathogenicity of human genetic variants. - Kircher, Martin; Witten, Daniela M; Jain, Preti; O'Roak, Brian J; Cooper, Gregory M; Shendure, Jay (Nat Genet, 2014)
Current methods for annotating and interpreting human genetic variation tend to exploit a single information type (for example, conservation) and/or are restricted in scope (for example, to missense changes). Here we describe Combined Annotation-Dependent Depletion (CADD), a method for objectively integrating many diverse annotations into a single measure (C score) for each variant. We implement CADD as a support vector machine trained to differentiate 14.7 million high-frequency human-derived alleles from 14.7 million simulated variants. We precompute C scores for all 8.6 billion possible human single-nucleotide variants and enable scoring of short insertions-deletions. C scores correlate with allelic diversity, annotations of functionality, pathogenicity, disease severity, experimentally measured regulatory effects and complex trait associations, and they highly rank known pathogenic variants within individual genomes. The ability of CADD to prioritize functional, deleterious and pathogenic variants across many functional categories, effect sizes and genetic architectures is unmatched by any current single-annotation method.
Keywords: Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; INDEL Mutation; Models, Genetic; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Selection, Genetic; Support Vector Machine